Changes in Nature Conservation-Relevant Public Participation Processes Through Digitalization: The Case of Germany - Stefan Heiland; Markus Günther; Brigitte Holzhauer; Florian Kern; Josephin Wagner (Land)
The literature shows that limited research has been conducted on the changes induced by digital means in public participation processes on plans whose implementation could have an impact on nature conservation and landscape development. To contribute to closing this research gap, 15 expert interviews were conducted to shed light on the use of digital tools in public participation processes in Germany. The analysis examined potential changes in the quantity and diversity of participants, timing and duration of involvement, tone and content, and the influence of participation on decision-making. The experts’ experiences vary widely, and knowledge must still be consolidated. The findings suggest that using digital instruments can increase the number of participants and the variety of social groups they represent. Other factors, such as personal interest and implications or potential for conflict, are more crucial to participating. However, digital tools allow for easier participation at various stages of participation if all necessary information is provided online. The tone of the discussion appears to be significantly influenced by the specific digital tool used for participation; for example, a plenary video session may unfold in an orderly manner, but the concurrent chat discussion can become chaotic or even insulting without strict facilitation. Digital tools might increase public interest in planning processes and lead to a higher relevance of citizens’ opinions in decision-making. However, this does not necessarily impact its outcome, as various opinions can neutralize each other. Observing this development more intensively seems necessary to take advantage of opportunities and counteract digitalization risks. Nonetheless, it can be concluded that digital formats cannot and should not replace analog forms of participation; rather, both should be combined in hybrid forms.